Decision Analysis Trading Foreign Exchange Berbasis Signaling Theory - Mochammad Rizaldy Insan Baihaqqy (Politeknik APP Jakarta, 2022)
The increase of investors in Indonesia demonstrates that there is a general understanding of the importance of investing. The exchange rate riddle phenomena in the link between exchange rates and macroeconomic fundamentals has prompted the development of a microstructure model approach to the foreign exchange market in the investing industry. The foreign exchange market structure model is a method for describing the movement of exchange prices in the foreign exchange market. In the foreign exchange market, the conventional assumption is that agents think that information generated from news can have an effect on exchange rate fluctuations. The purpose of this study is to undertake a descriptive analysis of the findings of prior studies on the link between macroeconomics and foreign exchange rate fluctuations. There is a wealth of information available about macroeconomics, most notably from numerous news sources. The theoretical analysis in this study employs signaling theory with an emphasis on investors, so that the study's findings can serve as a guide for investors interested in foreign currency market investing. The findings indicated that local and international macroeconomic negative news consistently had a substantial influence with a positive coefficient in a variety of nations. On the macroeconomic good news connection, consistently has a negative coefficient and a substantial effect. These findings indicate that as a country's economic situation deteriorates, foreign exchange prices rise. For example, when Indonesia's macroeconomic situation deteriorates, the Rupiah weakens and the Dollar strengthens, implying that when Indonesia's macroeconomic situation deteriorates, investors holding Dollars benefit. In the other direction, as Indonesia's macroeconomic situation improves, the Rupiah strengthens, resulting in losses for investors holding Dollars. This demonstrates that macroeconomics is a signal to which investors must respond when trading foreign exchange